Wetland habitat selection by woodland caribou as characterized using the Alberta Wetland Inventory - Brown, W. Kent; Rettie, W. James; Wynes, Bob; Morton, Kim (Rangifer, 2011)
We examined habitat selection by woodland caribou (Rangifer tarandus caribou) in northwestern Alberta based on a wetland classification system developed for the Alberta Vegetation Inventory. Our two objectives were to describe caribou habitat use, and to assess the utility of the wetland classification system in land-use planning on caribou range. We used a geographical information system to overlay the locations of radio-collared caribou on the habitat map. Using a "moving-window" analysis of habitat availability, we examined patterns of habitat selection by 16 individual female caribou during five seasons annually over two years. We did not detect significant differences in habitat selection patterns among seasons. Caribou showed significant preferences for both bogs and fens with low to moderate tree cover relative to marshes, uplands, heavily forested wetlands, water, and areas of human use. The wetland classification system appears to have value for broad-scale planning of industrial activity on caribou range. More-detailed descriptions of vegetation, especially understory species, are required to refine this system for operational-level forest harvest planning.